Comparison on the rhetorical promotional strategies used in performing art and visual art research articles - Ab Rahim, Ina Suryani; Abd Rashid, Salleh; Yaacob, Aizan; Abd Aziz, Noor Hashima (2015)
Articles on innovative research development and discussions on sustainable issues in Art and Design Education Research are welcomed by editors and publishers for the reason that sharing of knowledge would encourage beneficial development to the advancement of Arts and Design education and research.Consecutively, researchers of other disciplines are putting vigorous effort to publish their articles to the extent that promotional strategies are used to appeal the interest of the readers and editors in return increase the possibility of publication and citation. While studies found promotional strategies have permeated into the journal articles in Science and Technologies disciplines, not much has been discussed on whether the Arts and Design academicians promote their work in their journal article writing. Motivated by the understanding that utilization of the promotional strategy in journal article writing would benefit the Art and Design writers in publishing their work, this article investigated the use of promotional strategies in the Art and Design research articles.Putting the findings side by side, it was found that the Visual Arts articles utilized more recommended strategies in their writing compared to the Performing Arts articles. Compared to the Performing Art articles, the Visual Arts articles were found using more strategies that indicated the research gap and strategies that stated the value of their work. The comparison between the two also suggested direct and indirect attempt on using the strategies.